Decompressive craniectomy in cerebral venous thrombosis: a single centre experience. Issue 9 (16th April 2013) - Aaron, Sanjith; Alexander, Mathew; Moorthy, Ranjith K; Mani, Sunithi; Mathew, Vivek; Patil, Anil Kumar B; Sivadasan, Ajith; Nair, Shalini; Joseph, Mathew; Thomas, Maya; Prabhu, Krishna; Joseph, Baylis Vivek; et al.
Abstract : Background: Cerebral venous thrombosis (CVT) is an important cause for stroke in the young where the role for decompressive craniectomy is not well established. Objective: To analyse the outcome of CVT patients treated with decompressive craniectomy. Methods: Clinical and imaging features, preoperative findings and long-term outcome of patients with CVT who underwent decompressive craniectomy were analysed. Results: Over 10 years (2002–2011), 44/587 (7.4%) patients with CVT underwent decompressive craniectomy. Diagnosis of CVT was based on magnetic resonance venography (MRV)/inferior vena cava (IVC). Decision for surgery was taken at admission in 19/44 (43%), within 12 h in 5/44 (11%), within first 48 h in 15/44 (34%) and beyond 48 h in 10/44 (22%). Presence of midline shift of ≥10 mm (p<0.0009) and large infarct volume (mean 146.63 ml; SD 52.459, p<0.001) on the baseline scan influenced the decision for immediate surgery. Hemicraniectomy was done in 38/44 (86%) and bifrontal craniectomy in 6/44 (13.6%). Mortality was 9/44 (20%). On multivariate analysis (5% level of significance) age <40 years and surgery within 12 h significantly increased survival. Mean follow-up was 25.5 months (range 3–66 months), 26/35 (74%) had 1 year follow-up. Modified Rankin Scale (mRs) continued to improve even after 6 months with 27/35 (77%) of survivors achieving mRs of ≤2. Conclusions: This is the largest series on decompressive craniectomy for CVT in literature to date. Decompressive craniotomy should be considered as a treatment option in large venous infarcts. Very good outcomes can be expected especially if done early and in those below 40 years.